The Impact of Economic Shocks On Economic Growth in Iraq During the Period (2004-2018) - Safer, Jafer; Zahir, AbdulHamid (Humanities Journal of University of Zakho, 2020)
This research aims to study to determine the impact of economic shocks on economic growth in Iraq during the period (2004-2018), and the most important factors that affect economic growth have been identified. And represented in oil prices, the exchange rate, external debt and trade openness, which represent the independent variables of the model used, whereas, economic growth was expressed in gross domestic product as a dependent variable. The usual least squares method is used to estimate the model parameters. The unit root test and the cointegration test were also used. The pulse response functions were estimated to determine the impact of economic shocks on the Iraqi economy during the study period. It was found from the results of the estimation that the time series of the study has stabilized after taking the first differences, There is also a complementarity, that is, there is a long-term equilibrium relationship between the variables used, It was also found that the impact of economic shocks resulting from fluctuations in global oil prices was clear on the economic growth in Iraq.